IMPLEMENTATION OF E-PERFORMANCE POLICY IN WAJO REGENCY REGIONAL SECRETARIAT - Rizal, Rizal; Aslinda, Andi; Sakawati, Herlina; Ismail, Ismail (Jurnal Aktor, 2025)
This study aims to find out the Implementation of E-Performance Policy in the Wajo Regency Regional Secretariat. This study uses a qualitative approach and produces descriptive data. Data collection was used by observation, interview, and documentation techniques. The data obtained from this study were analyzed using data reduction, data presentation, withdrawal and conclusion testing. The results of this study show that the implementation of the E-Performance policy in the Wajo Regency Regional Secretariat has not been optimally implemented. The four indicators of the success of the implementation of policies that are implemented optimally are disposition, because it is seen from the honest attitude of the apparatus and their commitment in working on the implementation of E-Performance in the Wajo Regency Regional Secretariat. Furthermore, communication indicators have not been implemented properly, this is due to socialization about E-Performance which has not included employees as a whole. Human resource indicators have not been implemented optimally, this is due to the absence of special companions and there are still many employees who still have difficulty understanding the use of E-Performance. The indicators of bureaucratic structure have not been implemented properly, this is because there are no special regulations or standard operating procedures that regulate the use of E-Performance in the Wajo Regency Regional Secretariat